2022
DOI: 10.3389/fpsyg.2021.733050
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and Job Resources on Employees’ Job Insecurity During the First Wave of COVID-19: The Mediating Effect of Work Engagement

Abstract: The world of work has been severely affected by the COVID-19 pandemic due to the high instability observed in the labor market, bringing several new challenges for leaders and employees. The present study aims to analyze the role of organizational and job resources in predicting employees’ job insecurity during the first wave of the COVID-19 outbreak, through the mediating role of work engagement. A sample of 207 Portuguese employees participated (Mean age = 45 years old, SD = 9.92), of which 64.7% were women.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…The latest reviews on conservation of resource theory state that perceived stress or psychological ownership can act as the crucial underlying mechanisms to unpack the "black box" between resource allocation characteristics and distal receivers' behaviors (Chang et al, 2012;Singh et al, 2019). Job insecuritythe extent to which organizational employees perceive stress to maintain the continuity of the status quo and worry about threatened powerlessness (Vander Elst et al, 2014;Vieira Dos Santos et al, 2022)-may be stimulated by unconventional superior-subordinate interactions. Territorial consciousness represents the reinforcement of psychological ownership, which is largely triggered by senses of possession and affects employee behavioral strategies for specific targets (Jussila et al, 2015;Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The latest reviews on conservation of resource theory state that perceived stress or psychological ownership can act as the crucial underlying mechanisms to unpack the "black box" between resource allocation characteristics and distal receivers' behaviors (Chang et al, 2012;Singh et al, 2019). Job insecuritythe extent to which organizational employees perceive stress to maintain the continuity of the status quo and worry about threatened powerlessness (Vander Elst et al, 2014;Vieira Dos Santos et al, 2022)-may be stimulated by unconventional superior-subordinate interactions. Territorial consciousness represents the reinforcement of psychological ownership, which is largely triggered by senses of possession and affects employee behavioral strategies for specific targets (Jussila et al, 2015;Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, within the context of uncertainty, it is important for organizations to create a psychosocially safe space for employees to learn when mistakes happen. As organizations establish high psychosocial safety climate and learning climate, these serve as organizational resources that allow employee to be more engaged at work ( Vieira dos Santos et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researches showed that the work engagement was influenced by a lot of factors, mainly into two categories, namely internal factors and external factor (Mao et al, 2020 ). The internal factors contained regulatory emotional self‐efficacy (Lan et al, 2020 ), job satisfaction (Zhang et al, 2020 ) and performance feedback (Vieira Dos Santos et al, 2021 ), while the external factors contained job resources (Mukaihata et al, 2020 ), workplace bullying (Chan et al, 2020 ) and work overload (García‐Iglesias et al, 2021 ). However, there was a lack of research on the current situation of the work engagement of the Chinese male nurses and the research on the influencing factors of their work engagement.…”
Section: Introductionmentioning
confidence: 99%